A lightweight encryption and message authentication framework for wireless communication. Issue 3 (8th November 2022) - Wang, Shaoyu; Huang, Kaizhi; Ma, Keming; Xu, Xiaoming; Hu, Xiaoyan
Abstract: Confidentiality and authentication are two important security properties of wireless communication. There are currently two types of research in wireless communication security: one is based on cryptography, which can be too complicated for some wireless systems; the other is based on physical layer characteristics, which has some security problems and cannot work as well as the cryptography‐based method. In this paper, a lightweight encryption and message authentication framework for wireless communication is proposed. The proposed framework has lower complexity than the cryptography‐based method and works more securely and efficiently than the classical physical layer method. For the encryption, a physical layer offered chain key (PHYLOCK) structure is proposed to generate one‐time keys, which are then XOR‐ed with the plaintext to generate the ciphertext. A security analysis of PHYLOCK is performed and it is proved that it has better security features than the traditional physical layer key generation. For the message authentication, three types of PHYLOCK‐CRC‐based message authentication schemes are developed whose generator polynomial is determined by one‐time keys generated by PHYLOCK. PHYLOCK‐CRC‐based message authentication detects not only random errors introduced by noises but also malicious attacks. The error‐detecting and anti‐attack capabilities are analyzed mathematically. Compared to the standard CRC, PHYLOCK‐CRC‐based message authentication has a decline in error correction capability but is enhanced with cryptographic security features. Monte‐Carlo simulations are provided to evaluate the proposed scheme.